Lattice distortion and orbital hybridization in NdFeO3–PbTiO3 ferroelectric thin films. Issue 4 (21st December 2015) - Zhao, Hanqing; Miao, Jun; Zhang, Linxing; Rong, Yangchun; Chen, Jun; Deng, Jinxia; Yu, Ranbo; Cao, Jiangli; Wang, Huanhua; Xing, Xianran
Abstract : Large lattice distortion and strong orbital hybridization lead to considerable ferroelectric value in x NdFeO3 –(1 − x )PbTiO3 thin films at x = 0.1. Abstract : Single-phase x NdFeO3 –(1 − x )PbTiO3 thin films with different dopant contents were fabricated on the Pt(111)/Ti/SiO2 /Si substrate by a sol–gel route. Grain size was influenced by the dopant content effectively. A synchrotron radiation X-ray diffraction study revealed a reduced tetragonality ( c / a ) of the PbTiO3 lattice in the films. Distortion of the TiO6 octahedron was weakened, as investigated by Raman scattering and X-ray absorption spectra. An electronic structural study indicated that the hybridizations between O 2 p and Pb 6 s and Ti 3 d orbitals were weakened. The decrease of lattice distortion and orbital hybridization gives rise to degradation of the ferroelectric nature in the films.